Mesenchymal Stem Cells from Chronic Pancreatitis Patients Show Comparable Potency Compared to Cells from Healthy Donors. (24th January 2019) - Wang, Jingjing; Zhang, Yong; Cloud, Colleen; Duke, Tara; Owczarski, Stefanie; Mehrotra, Shikhar; Adams, David B.; Morgan, Katherine; Gilkeson, Gary; Wang, Hongjun
Abstract: Mesenchymal stem cells (MSCs) are proven to be beneficial in islet transplantation, suggesting a potential therapeutic role of them in total pancreatectomy with islet autotransplantation (TP-IAT) for chronic pancreatitis (CP) patients. We investigated whether MSCs derived from CP patients are suitable for use in autologous cell therapy. MSCs from healthy donors (H-MSCs) and CP patients (CP-MSCs) were studied for phenotype, colony formation potential, multilineage differentiation ability, proliferation, senescence, secretory characters, and immunosuppressive functions. The potential protective effect of CP-MSCs was evaluated on hypoxia-induced islet cell death. Cell surface markers were similar between H-MSCs and CP-MSCs, as well as the ability of colony formation, multilineage differentiation, secretion of vascular endothelial growth factor and transforming growth factor (TGF-β), senescence, and inhibition of T cells proliferation in vitro. We found that growth differentiation factor 6 and hepatocyte growth factor ( HGF ) were significantly downregulated, whereas TGFβ and matrix metalloproteinase-2 were significantly upregulated in CP-MSCs compared with H-MSCs, among 84 MSC-related genes investigated in this study. MSCs from CP patients secreted less HGF, compared with the H-MSCs. A higher interferon-γ-induced indoleamine 2, 3-dioxygenase expression was observed in CP-MSCs compared to H-MSCs. Moreover, CP-MSCs prevented hypoxia-induced β cell deaths to a similar extent as H-MSCs. Regardless of moderate difference in gene expression, CP-MSCs possess similar immunomodulatory and prosurvival functions to H-MSCs, and may be suitable for autologous cell therapy in CP patients undergoing TP-IAT. Stem Cells Translational Medicine 2019;8:418–429 : Abstract : Mesenchymal stem cells (MSCs) derived from chronic pancreatitis (CP) patients exhibited similar protective effects on hypoxia-induced islet cell death compared to MSCs derived from healthy donors, despite moderate difference in gene expression profile and the secretion of growth factors, suggesting a potential therapeutic role of them in total pancreatectomy with islet autotransplantation for CP patients.